Investigation of static and dynamic mechanical loads on light-weight PV modules for offshore floating applications - Kyranaki, Nikoleta; Nivelle, Philippe; Bouguerra, Sara; Casasola Paesa, Marta; De Jong, Richard; Delbeke, Oscar; Spannan, Lars; van der Heide, Arvid; Kaaya, Ismail; Moschner, Jens; Morlier, Arnaud; Daenen, Michael (Engineering Structures, 2024)
Photovoltaic (PV) systems are significant for the transition towards renewable energy. However, their expansion is constrained by the scarcity of suitable land in proximity to electric grids. To address this issue, floating PV is a promising solution. Ensuring the robustness of floating PV installations remains a major concern, particularly regarding the mechanical load due to strong winds in open water. This study aims to assess the impact of wind on floating PV modules, by considering real wind speed values occurring at the North Sea. To achieve this objective, the influence of PV module configuration, such as inclination, is examined. Moreover, different thicknesses of PV glass are considered to find an optimum between mechanical stability and material consumption. Lastly, a resonance vibration test is performed and compared to simulations to estimate the effects of vibration on PV module stress. The findings indicate that a low inclination installation is preferable, and a glass-glass PV module with a 2.5 mm glass thickness can withstand static and dynamic mechanical loads, although long-term durability requires further investigation. Additionally, it is crucial for the standard Dynamic Mechanical Load (DML) test to include higher pressure values and an extended vibration test at the resonance frequency with the highest measured acceleration, identified after a frequency sweep. sponsorship: FOD Economie, Energietransitiefonds|project MarineSPOTS status: Published online